Bank Risk and Industry Competition on Bank Profitability: Evidence from China after the global financial crisis (2009-2014) - Shi, Xiaolin (2016)
As a significant component of the financial system, Chinese banking industry plays a key role in the economic growth of China. In past decades, numerous reforms in the banking sector contribute to the formation of a competitive industry as well as the enhancement of bank performance. Nevertheless, higher level of competition in the banking sector does not inevitably contribute to the the enhancement of bank profitability. As argued by the structure-conduct-performance (SCP) hypothesis, the colluding behaviors of banks in a banking industry with high level of concentration contributes to the abnormal profits earned by banks in this sector. Compared to other countries, there is a considerably high concentration in Chinese banking market. On the basis of the annual report derived from the regulatory authority in China, that is, China Banking Regulatory Commission (CBRC, 2015), the assets of five state-owned commercial banks (SOCBs), which are also the largest five banks in Chinese banking industry, account for 41.4%, of the total assets in Chinese banking sector in 2014. Although this ratio keeps decreasing from 51.9% in 2009, it is still higher than some developed countries in Europe, such as Germany (32.4%), United Kingdom (38.9%) and Austria (36.8%) (European Central Banks, 2015). With regards to joint-stock commercial banks (JSCBs) as well as city commercial banks (CCBs) in China, these figures remain the growing trend, from 15.0% and 11.0% in 2009 to the highest ratios of 18.2% and 16.5% in 2014, respectively (CBRC, 2015).